Efficacy of the Health Belief Model in Enhancing Weight Loss Behaviors to Prevent Stroke among Overweight and Obese Geriatrics Homes Residents in Baghdad City - Arkan Bahlol Naji; Mohmmed Qassim Baktash (Kufa Journal for Nursing Sciences)
Background: Stroke is the third leading cause of death in Iraq exceeding only by coronary heart disease and war related death. Ageing with overweight plays a critical role in predisposing people to stroke; weight loss behaviors can have profound effect in protecting seniors with obesity from stroke.